Ryan Rusk: capstone - Rusk, Ryan, artist (Colorado State University. Libraries, 2026)
The artist's statement: As a potter, clay is my collaborator, and I feel I am a part of a lineage of humanity that is as old and as important as our species. Ceramic material and spirit grounds us, supporting and enriching our lives. Working with clay reminds me of my own humanity as well as my relationship to humanity as a whole. I am interested in the alchemical transformation of atmospheric firing. It allows me to collaborate with the firing process and materials in a way where I give up some control, and every particle going into the firing gets to have its own voice, all working together towards a common goal. My work explores themes of liminal space, ritual, and functionality, inspired by intuitive personal mythos and the reciprocal process of working with the elements that work together to become formed objects. Inspired by the forms and surfaces of the conservatory, this body of work takes the collaboration of clay, salt, wood, and fire and merges with the space and plants growing around it, allowing these pieces to become part of their environment.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery